Plurilingual Identities of ELT Students: A Preliminary Study - Hardianti Hardianti; Muhammad Basri; Sahril Sahril (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
Plurilingualism is another breakthrough of multilingualism. It is believed to be able to promote learning in cross cultural settings. This study focuses on finding out students’ plurilingual identities within the context of Indonesian higher education students majoring in English Language Teaching (ELT). This is a mixed-method study that used a survey to get quantitative data and a focus group to help the researcher get the qualitative data. More than sixty students of a private university in Banggai Regency have participated in the survey, however only five that had been taken to participate in the focus group. The results found that most of the students come from mixed marriage parents from different ethnicities backgrounds. Within more than six months of acquaintance with the students, various ways have been revealed from the way the students explain their plurilingual identity. Many students could not identify and describe their plurilingual identities properly during the survey study. In the focus group, students were asked to describe their plurilingual identities through pictures description. The pictures were drawn by the students. The data were analyzed through content analysis. Finally, this paper is expected to portrait plurilingual identities of ELT students as well as strengthens their cross-cultural understanding in the Indonesian higher education context.